Neutron strain tomography - Abbey, B (2012)
This thesis concerns the development of a technique known as ‘neutron strain tomography’, in order to non-destructively map, in three dimensions, residual elastic strain. The fundamental idea behind this research is that the strain values provided by through thickness transmission strain measurements are the result of averaging a number of strains within the sample. If a two-dimensional energy-resolving pixellated detector is used to record the transmission strains, a spatially resolved two-dimensional image of the average strain within the sample is obtained. This implies that if one records two-dimensional average strain data from the same sample from a number of different orientations there may be a route to reconstructing a set of higher dimensional volume data based on these two dimensional datasets. The principle aim of this thesis has been to help develop neutron strain tomography into a viable tool for three-dimensional strain imaging. The main themes explored in this research are the generalisation of the method to arbitrary strain fields and its extension to high resolution strain 'imaging'. Solutions and challenges associated with the first theme are outlined in chapters 2 and 3 which lay the theoretical foundations for the algorithms we employ in this research and the results obtained using these algorithms respectively. The second theme, resolution, is discussed in chapter 4 where the possibilities offered by high-resolution, energy resolving, neutron detectors is discussed in the context of neutron strain tomography. The descriptions of the algorithms, the comparison of possible approaches, and the improvements afforded by new detector technologies is intended to serve as an entry point guide for researchers wishing to further continue this work.